LEARNING ARABIC LANGUAGE WITH GENDER NEUTRAL INSIGHT AT MAULANA MALIK IBRAHIM STATE ISLAMIC UNIVERSITY OF MALANG - Dewi Chamidah; Bisri Mustofa; Inayatur Rosyidah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Arabic language actually contains sexism. Therefore, learning Arabic with a gender neutral perspective is absolutely necessary so that the alignments towards the Adam and the marginalization of the Eve can be straightened out. Research learning Arabic language with gender neutral insight at Maulana Malik Ibrahim State Islamic University of Malang is a library research. In addition, this also includes the type of qualitative research. The documentary method was chosen for data collection techniques. The contribution of learning gender-oriented Arabic language at UIN Maulana Malik Ibrahim Malang was explored through interviews and questionnaires. The data analysis technique used is qualitative data analysis with data validity methods in the form of participation, perseverance of observation, triangulation and adequacy of references. Gender-based Arabic learning in the Special Arabic Language Development Program (PPBA) and Arabic education department includes: Learning planning process, Teaching and learning interactions, Class management and the use of gender responsive language and Arabic learning with gender-neutral insight in the Special Program for Arabic Language Development (PPBA) and the Arabic Education majors as a whole have a positive impact.